CEBPB promotes gastrointestinal motility dysfunction after severe acute pancreatitis via the MALAT1/CIRBP/ERK axis. (April 2023) - Lai, Lixia; Wang, Guiliang; Xu, Linfang; Fu, Yunhui
Abstract: Severe acute pancreatitis (SAP) is a kind of reversible inflammatory process of the exocrine pancreas with gastrointestinal motility dysfunction involved. Studies have highlighted the role of long noncoding RNA metastasis associated lung adenocarcinoma transcript 1 (MALAT1) in AP. However, the mechanism underlying its role in the gastrointestinal motility dysfunction remains undefined. Hence, we explored the regulatory role of MALAT1 in gastrointestinal motility dysfunction following SAP. Then, the expression of CCAAT/enhancer-binding protein beta (CEBPB), MALAT1 and cold-inducible RNA binding protein (CIRBP) was detected in plasma of SAP patients and pancreatic and intestinal tissues of SAP mouse models with their correlation analyzed also. Additionally, the effect of MALAT1 on the pancreatic and intestinal injury, expression of inflammatory factors and the ERK pathway-related genes as well as gastrointestinal motility dysfunction was assessed using ectopic expression and depletion experiments. CEBPB, MALAT1 and CIRBP were highly expressed in plasma of SAP patients and pancreatic and intestinal tissues of SAP mice. Further analysis showed that knockdown of MALAT1 could alleviate pancreatic and intestinal injury, reduce inflammation, and prevent gastrointestinal motility dysfunction in SAP mice. The transcription factor CEBPB could bind to the promoter region of MALAT1, thus activating the transcription of MALAT1. MALAT1 interacted with CIRBP and inhibited the degradation of CIRBP, leading to activated extracellular signal-regulated kinase (ERK) pathway and the resultant gastrointestinal motility dysfunction. In conclusion, CEBPB exhibits a promoting activity towards gastrointestinal motility dysfunction in SAP by pumping up MALAT1 expression and activating the CIRBP-dependent ERK pathway. Highlights: MALAT1 silencing results in attenuated gastrointestinal motility dysfunction in SAP. CEBPB promotes MALAT1 transcription by binding to the MALAT1 promoter. MALAT1 maintains the stability of CIRBP by inhibiting its ubiquitination. MALAT1 activates the ERK pathway by stabilizing CIRBP protein. This study provides a new therapeutic target for SAP.